Navigating White News Asian American Journalists at Work. - Oh, David C. (Rutgers University Press, 2023)
"Combining critical race studies with cultural production studies, Navigating White News: Asian American Journalists at Work is the only academic book to examine the ways that racial identification and activation matters in their understanding of news. This adds to the existing literature on race and the sociology of news by examining intra-racial differences in the ways they navigate and understand White newsrooms. Employing in-depth interviews with twenty Asian American journalists, who are actively working in large and small newsrooms across the United States, the book argues that Asian American reporters for whom racial identities are salient questioned what counted as news, questioned the implicitly White perspective of objectivity, and actively worked toward providing more complex, substantive coverage of Asian American communities. For Asian American reporters for whom racial identity was not meaningful, they were more invested in existing professional norms. Regardless, all journalists understood that news is a predominantly and culturally White institution"--